(3GdhGbY GdEaJQGVj Hjf GdYde h Gdaf (B/s - (3SefOQ, CSQGQ YHGSs ((3GdEScfOQjI (B:s (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQ ,s, 2020)
(3GdcJGH SjMJhj Ydi GdYOjO ef GdcdeGJ h GdeUWdMGJ GdMOjKI abO befG HYfd agQSG HJaSjQ GNJUGQGJ ddcdeGJ GdMOjKI ddeUWdMGJ GdJj hQOJ HGdcJGH h SjJHY GdcJGH GdefgL GdhUaj GdJMdjdj ddNQhL HGge GdGSJfJGLGJ h GdJhUjGJ Vef GdJLQHI GdYGdejI aj cd ecGf h HMOhO ReGfjg ef (B1950 (3hUhdG Gdi hbJfG GdMGdj aj GdbQf GdCNjQ (B2020(3eY GdESJeQGQ HWQM GdSDGd GdCJj eG GKQ GdhGbY GdGaJQGVj aj GdMjGI GdeYGUQs
(3HHdjhZQGajG (B: (3U(B.215-230s
Keywords: (3GdJcfhGhLjGs; (3GdYGde GdGaJQGVjs